Collecting data of human choice using Problem Solving Environment and modeling human behavior - Maeda, Taiyo; Matsumoto, Shigeru; Murata, Tadahiko; Yang Cao (2010 5th International Conference on Computer Sciences and Convergence Information Technology, 2010)
This paper reports a web-based Problem Solving Environment (PSE) system to consider models for human choice behavior. This system collects behavioral data which human subjects chose facilities. Using this system, they choose a facility according to the information such as congestion level for the facility they chose in the previous turn. We examine several models to simulate behaviors of human choice. As a result, we could find a model that improves the similarity between the simulated and actual data.